Spontaneous broad ligament rupture following uncomplicated vaginal delivery: A case report - Martina Beretta; Philippe Demoustier; Gabriel Charaf (Case Reports in Women's Health)
Spontaneous hemoperitoneum in the postpartum period is rare and potentially fatal, especially following an uncomplicated vaginal delivery. We present the case of a 37-year-old woman who developed hypovolemic shock and acute abdominal pain four days postpartum. Imaging revealed massive intra-abdominal bleeding. Emergency laparotomy identified a spontaneous rupture of the left broad ligament with 3 l of hemoperitoneum. Surgical repair and resuscitation were successful. This case underlines the importance of considering internal bleeding in postpartum patients with abdominal symptoms, even in the absence of obstetric complications.